Особливості принципів земельного права України серед засобів мінімізації юридичних дефектів - Коваленко, Т.; Kovalenko, T. (Східноєвропейський національний університет імені Лесі Українки, 2018)
У статті проведено аналіз загальних та особливих ознак принципів земельного права України, специфіки їх нормативного закріплення, а також їх ефективності як загально-правового засобу мінімізації колізій, прогалин та інших юридичних дефектів у механізмі правового регулювання земельних відносин в Україні; виявлено фактори, які ускладнюють застосування принципів земельного права як ефективних засобів мінімізації юридичних дефектів у земельній сфері. In today's conditions, when the number of normative regulations is constantly increasing and regulatory acts are rapidly updated, the role of legal principles substantially increases, in particular as one of the means of minimization of legal defects in land relations regulation in Ukraine. Land law principles inherent common features of legal principles: special legal nature; universality; supreme imperative; general binding; general, fundamental and regulatory nature; objective conditionality; stability; systemic character; formal certainty. The study of the practice of applying the norms of land legislation and special literature gives grounds to say that in today's conditions the application of land law principles as effective means of legal defects minimization in the regulation of land relations is complicated by certain factors. First, not all sectoral principles of land law have been reflected in Art. 5 of the Land Code of Ukraine. Secondly, certain principles, enshrined in Art. 5 of the Land Code of Ukraine, contradict the general principles of law, are not consistent with each other and with other norms of land law. Thirdly, some principles of land law, that are fixed in Art. 5 of the Land Code of Ukraine, are not the principles of law by their nature, which complicates their application in practice. Fourthly, in Ukrainian land science there is a problem of identifying those principles of law, that actually regulate land relations, and distinguishing them from legally prescribed declarative provisions, called «principles» of land legislation.
Features of Principles of Land Law of Ukraine among Means for Legal Defects Minimization
Keywords: земельне право; земельні правовідносини; земельне законодавство; ефективність правового регулювання; колізії; мінімізація юридичних дефектів; принципи права; прогалини; юридичні дефекти; effectiveness of legal regulation; gaps; land law; land legislation; land relations; legal conflicts; legal defects; minimization of legal defects; principles of law